1982
DOI: 10.1093/oxfordjournals.aob.a086387
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of Gibberellin and Sucrose-promoted Flower Bud Growth in Gladiolus

Abstract: A critical stage in flower bud growth in the spike of Gladiolus which is initiated by gibberellic acid (GA 3) and sustained by sucrose has been identified. This corresponds to the stage at which separation of the outer bract occurs. In buds at different developmental stages isolated and held in water, it is the same bud stage that first shows increased growth. Buds not induced by light were shown to respond more significantly to GA 3 and sucrose than those induced by light. Since the separation of the outer br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
(4 reference statements)
1
3
0
Order By: Relevance
“…Similar trend of results was reported by Rao and Ram (1982) on Gladiolus sp. and EL-Mokadem (1991) on bird of paradise.…”
Section: Floret Full Opening Period (Day)supporting
confidence: 91%
“…Similar trend of results was reported by Rao and Ram (1982) on Gladiolus sp. and EL-Mokadem (1991) on bird of paradise.…”
Section: Floret Full Opening Period (Day)supporting
confidence: 91%
“…In most studies, GA3 has been ap plied directly to the developing bud (5,6,7,8,13,18). In carnation (2) and gladiolus (14), GA3, in vase solutions, promoted bud opening and growth of cut flowers. Zieslin et al (18) reported growth stimulation by GA3 of isolated petals cultured in a liquid medium containing nutrients.…”
mentioning
confidence: 97%
“…In the most complete studies of this involvement, gibberellins seem to be important (Blake, 1969;deJong and Bruinsma, 1974;Jeffcoat, Scott and Harris, 1969;Plack, 1958;Rao and Mohan Ram, 1979;Zieslin, Biran and Halevy, 1974), but the other hormones (auxins, cytokinins, ethylene, and abscisic acid) may also be implicated especially when hormone interactions are considered (deJong and Bruinsma, 1974). The effects of applied hormones, hormone synthesis, and hormone-action inhibitors have been used to help demonstrate regulatory roles for these hormones (deJong and Bruinsma, 1974;Rao and Mohan Ram, 1979). Studies showing parallel or inverse variation of endogenous hormone levels and corolla elongation add further support to the roles for the plant hormones in this growth process.…”
mentioning
confidence: 99%
“…The roles ofthe plant hormones are well-established, but vary from species to species. Gibberellins-Hormone application studies have almost unanimously implicated the gibberellins as important regulators of corolla growth (Alpi et al, 1976;Berghoefand Bruinsma, 1979a, b;Blake, 1979;deJong and Bruinsma, 1974;Harris et al, 1969;Plack, 1958;Rao and Mohan Ram, 1979;Zieslin et aI., 1974). The exceptions to this are the corollas offemale Begonia flowers (Berghoef and Bruinsma, 1979a), which are inhibited by gibberellins, and Momordica flowers (Prakash, 1977), which do not respond to gibberellins.…”
mentioning
confidence: 99%